Implementation Double-Track System Criminal Sanctions and Rehabilitation Against Narcotic Abusers - Chaidar, Muhamad; Budiarsih, Budiarsih (Faculty of Law, Universitas Pattimura, 2022)
Introduction: The application of sanctions is regulated in Law no. 35 of 2009 concerning Narcotics, which tends to impose criminal sanctions, does not have an impact, in fact there are more narcotics abusers. In accordance with the mandate of Law no. 35 of 2009 concerning narcotics, addicts and victims of narcotics abuse are entitled to rehabilitation, both medical rehabilitation and social rehabilitation. In general, addicts and victims of narcotics abuse have not been able to access rehabilitation services, especially addicts and victims of narcotics abuse who are in prisons or detention centers.Purposes of the Research: focus of the formulation in this research is How to Analyze the Meaning of Medical Rehabilitation Obligations for Narcotics Addicts?.Methods of the Research: The method used in this research is the normative juridical method and the law approach as well as the conceptual approach. They are in medical rehabilitation and/or social rehabilitation institutions.Results of the Research: Researchers suggest to the Government and the DPR to add explanations for narcotics addicts in Article 54 of Law Number 35 of 2009 concerning Narcotics, by including the amount of medical rehabilitation financing provided to narcotics addicts in Law Number 35 of 2009 concerning Narcotics. Prior to the promulgation of the amount of medical rehabilitation financing, regarding the provision of medical rehabilitation for narcotics addicts it will be easier to implement, and for the public to increase participation in the prevention of narcotics addicts and accessibility to the settlement of litigation and non-litigation cases.